Alcohol amination with aminoacidato Cp*Ir(III)-complexes as catalysts: dissociation of the chelating ligand during initiation - Wöckel, Simone; Pleßow, Philipp; Schelwies, Mathias; Brinks, Marion K.; Rominger, Frank; Hofmann, Peter; Limbach, Michael (ACS catalysis, 2014)
The use of aminoacidato Cp*Ir(III)-complexes in catalytic alcohol amination reactions of primary and secondary alcohols with amines permits to carry out these transformations at very mild reaction conditions without the use of an additional base. Herein we discuss the fate of the chelating aminoacidato ligands upon initiation of Cp*Ir(III)-complexes from a mechanistic perspective. Catalyst initiation has been followed by NMR using isotopically labeled 13C,15N-glycinato complexes.